2016
DOI: 10.1021/acsami.6b04571
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Interactions and Biological Responses of Emerging Two-Dimensional Materials and Aromatic Amino Acid Complexes

Abstract: The present work experimentally investigates the interaction of aromatic amino acids viz., tyrosine, tryptophan, and phenylalnine with novel two-dimensional (2D) materials including graphene, graphene oxide (GO), and boron nitride (BN).Photoluminescence, micro-Raman spectroscopy, and cyclic voltammetry were employed to investigate the nature of interactions and possible charge transfer between 2D materials and amino acids. Graphene and GO were found to interact strongly with aromatic amino acids through π−π st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
(85 reference statements)
1
26
0
Order By: Relevance
“…All other ENMs used in the study: titanium dioxide (TiO 2 ), iron oxide (Fe 2 O 3 ), magnesium oxide (MgO), boron nitrite sizes ultrafine (BN-UF) and microfine (BN-MF), zinc oxide (ZnO), silica dioxide sizes 30 nm (SiO 2 -30) and 60 nm (SiO 2 -60), and copper oxide (CuO) were purchased from US Research Nanomaterials, Inc and stored as a dried powder at 4 °C until ready for assay preparation. Two-dimensional boron nitride (BN) was synthesized by chemical exfoliation of bulk BN (purchased from Graphene supermarket) using a Branson ultrasonic tip (1/8″ diameter, 250 W)5556. ZnO nanoparticles were synthesized using a polyol method through drop-wise addition of aqueous Zn acetate and poly-vinylpyrrolidone (PVP) at 100 °C57.…”
Section: Methodsmentioning
confidence: 99%
“…All other ENMs used in the study: titanium dioxide (TiO 2 ), iron oxide (Fe 2 O 3 ), magnesium oxide (MgO), boron nitrite sizes ultrafine (BN-UF) and microfine (BN-MF), zinc oxide (ZnO), silica dioxide sizes 30 nm (SiO 2 -30) and 60 nm (SiO 2 -60), and copper oxide (CuO) were purchased from US Research Nanomaterials, Inc and stored as a dried powder at 4 °C until ready for assay preparation. Two-dimensional boron nitride (BN) was synthesized by chemical exfoliation of bulk BN (purchased from Graphene supermarket) using a Branson ultrasonic tip (1/8″ diameter, 250 W)5556. ZnO nanoparticles were synthesized using a polyol method through drop-wise addition of aqueous Zn acetate and poly-vinylpyrrolidone (PVP) at 100 °C57.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect validations can be performed by comparing the binding preferences of amino acids on graphene with the corresponding observations from ab initio, simulations, and wet-laboratory studies. [45,71,[81][82][83][84][85] The binding preferences of the amino acids on graphene estimated in our study and that reported in the literature are summarized in Fig. 4.…”
Section: B Free Energy Of Adsorption Of Amino Acidsmentioning
confidence: 97%
“…Indirect validations can be performed by comparing the binding preferences of amino acids on graphene with the corresponding observations from ab initio, simulations, and wet-laboratory studies. [45,71,[81][82][83][84][85] The binding preferences of the amino acids on graphene estimated in our study and that reported in the literature are summarized in Fig. 4.…”
Section: B Free Energy Of Adsorption Of Amino Acidsmentioning
confidence: 97%